SEMINAR PENGEMBANGAN PROGRAM APLIKASI AL-QUR'AN INDONESIA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR'AN TERHADAP SISWA SMPN 1 JANGKAR - Zaehol Fatah; Rinayatul Fadilah (CV. Denasya Smart Publisher, 2026)
The seminar on introducing the Al-Qur'an application in education plays a crucial role in improving students' understanding of the Quran at SMPN 1 Jangkar. The Al-Qur'an application is a digital learning medium that can help students recognize the hijaiyah letters, tajweed, and pronounce the Quran more accurately. The seminar involved delivering material and practicing the application directly, enabling students to understand the available features and use them independently. The data collection instrument used a closed-ended questionnaire to assess students' responses to the seminar and the use of the Al-Qur'an application. The results showed an increase in students' understanding of the Quran and a positive response to the application's use as a learning medium. This activity also encourages the use of digital technology in Quran learning in schools.